Keeping it Safe: Energy Conservation=More Money - Mary N. Harrison (EDIS)
Heating and cooling your home uses more energy and takes up more money than any other system in your home. No matter what kind of heating, ventilation, and air-conditioning system you have, you can save money and increase comfort by properly maintaining the equipment. This document is FCS5233-04, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.